Faktor-Faktor yang Mempengaruhi Kepuasan dan Loyalitas Perajin Gula Semut terhadap Model Social Enterpreneurship di CV Agro Berdikari - Putri, Dindy Darmawati; Utami, Dewanti Risa; Fitri, Natania Dwi Rahma (Hasanuddin University, 2025)
The research aimed to: (1) identify the social entrepreneurship cooperation model of CV Agro Berdikari, which is applied to palm sugar craftsmen. (2) Analyzing the factors that influence the satisfaction of palm sugar craftsmen towards the social entrepreneurship cooperation model at CV Agro Berdikari. (3) Analyzing the factors that influence the loyalty of palm sugar craftsmen towards the social entrepreneurship cooperation model at CV Agro Berdikari. (4) Analyzing the influence of palm sugar craftsmen's satisfaction on loyalty to CV Agro Berdikari. The research method used was qualitative and quantitative, using a survey method. The sample calculation used the proportional stratified random sampling method with 60 respondents. Data were collected using questionnaires, interviews, observations, and documentation. The data analysis used is descriptive and PLS-SEM. The results of the research indicate that: (1) The social entrepreneurship model applied by CV Agro Berdikari to the mentored craftsmen is in the form of programs that provide economic and social benefits. (2) Factors that influence the satisfaction of palm sugar craftsmen towards the social entrepreneurship model at CV Agro Berdikari are service quality, convenience, selling price, social support, and social business assistance. (3) Factors that influence the loyalty of palm sugar craftsmen towards the social entrepreneurship model at CV Agro Berdikari are service quality, social support, and social business assistance, while convenience and selling price do not have a positive and significant effect on loyalty. (4) The effect of palm sugar craftsman satisfaction on loyalty to CV Agro Berdikari is not positive and not significant.